Macroeconomic Aspects of European Integration: Fiscal Policy, Trade Integration and the European Business Cycle - Jesús Crespo-Cuaresma; Michael Pfaffermayr; Octavio Fernández Amador; Catherine Keppel (FIW - Research Centre International Economics, 2011)
We analyze the role of fiscal policy and intra-European trade in business cycle synchronization in the EU for the period 1995-2008. There is a broad consensus that the relationship between fiscal policy and business cycle comovements and between trade integration and cyclical synchronization are subject to endogeneity problems. We instrument fiscal budget surplus by means of (exogenous) political determinants of fiscal policy acknowledged by the literature, while trade integration is instrumented using covariates which summarize the integration status of countries in the sample, GDP per capita differences with respect to the EU and trade specialization within the EU framework. Our results show that both fiscal policy and trade integration are important determinants of cyclical synchronization. We can conclude that once a high degree of trade integration is reached by countries involved in the European integration process, the role of fiscal policy is particularly relevant and differences in fiscal shocks should be analyzed in detail as a source of coherence in cyclical comovements in Europe. Furthermore, fiscal deficits are shown to be an important potential source of idiosyncratic macroeconomic fluctuations, especially in the eurozone. Our results confirm the rationale of monitoring fiscal developments to assess the adequacy of potential future EMU countries and the need for a broad agreement concerning fiscal policy at the EU level.
Keywords: E32; E62; F15; 330; Monetary union; business cycles; synchronization; trade integration; fiscal policy